Primum non nocere – The effects of sodium hypochlorite on dentin as used in endodontics. (1st October 2017) - Gu, Li-sha; Huang, Xue-qing; Griffin, Brandon; Bergeron, Brian R.; Pashley, David H.; Niu, Li-na; Tay, Franklin R.
Graphical abstract: Abstract: The medical literature is replete with the maxim 'primum non nocere', cautioning health care providers to avoid doing any harm to human subjects in their delivery of medical care. Sodium hypochlorite (NaOCl) is a well-established irrigant for root canal treatment because of its antimicrobial and organic tissue remnant dissolution capability. However, little is known about the deleterious effect of this strong oxidizing agent on the integrity of human mineralized dentin. Iatrogenically-induced loss of dentin integrity may precipitate post-treatment root fracture and has potential medico-legal complications. In the present work, transmission electron microscopy provided evidence for collagen destruction in the surface/subsurface of dentin treated with high NaOCl concentrations and long contact times. Size exclusion chromatography showed that the hypochlorite anion, because of its small size, penetrated the water compartments of apatite-encapsulated collagen fibrils, degraded the collagen molecules and produced a 25–35 µm thick, non-uniform "ghost mineral layer" with enlarged, coalesced dentinal tubules and their lateral branches. Fourier transform-infrared spectroscopy identified increases in apatite/collagen ratio in NaOCl-treated dentin. The apatite-rich, collagen-sparse dentin matrix that remained after NaOCl treatment is more brittle, as shown by the reductions in flexural strength. Understanding the deleterious effects of NaOCl on mineralized dentin enables one to balance the risks and benefits in using high NaOCl concentrations for lengthy periods in root canal debridement. Delineating the mechanism responsible for such a phenomenon enables high molecular weight, polymeric antimicrobial and tissue dissolution irrigants to be designed that abides by the maxim of 'primum non nocere' in contemporary medical practices. Statement of Significance: The antimicrobial and tissue-dissolution capacities of NaOCl render it a well-accepted agent for root canal debridement. These highly desirable properties, however, appear to be intertwined with the untoward effect of collagen matrix degradation within mineralized dentin. Because of its small size, the hypochlorite anion is capable of infiltrating mineralized collagen and destroying the collagen fibrils, producing a mineral-rich, collagen sparse ghost mineral matrix with reduced flexural strength. Findings from the present work challenge the biosafety of NaOCl when it is used in high concentrations and for lengthy time periods during root canal treatment, and laid the background work for future biomaterials design in debridement of the canal space.